A Comparison of Retrograde Intrarenal Surgery and Percutaneous Nephrolithotomy for Management of Renal Stones ?2 CM - Sari, Sercan; Ozok, Hakki Ugur; Cakici, Mehmet Caglar; Ozdemir, Harun; Bas, Okan; Karakoyunlu, Nihat; Sagnak, Levent; Senturk, Aykut Bugra; Ersoy, Hamit (Urology Journal, 2017)
Purpose: In this retrospective study, we aimed to compare the outcomes in patients who have been treated withpercutaneous nephrolithotomy (PNL) and retrograde intrarenal surgery (RIRS) on renal stones ≥ 2 cm size. Materials and Methods: We evaluated patients who underwent PNL or RIRS for renal stones ≥ 2 cm size betweenNovember 2011 and November 2014. Stone size, operation, fluoroscopy and hospitalization time, success rates,stone-free rates and complication rates were compared in both groups. Patients were followed for three months. Results: 254 patients were in the PNL Group. 185 patients were in the RIRS Group. The mean age was 46.88 and48.04 years in PNL and RIRS groups, respectively.The patient and stone characteristics (age, gender, Body Mass Index, kidney anomaly, SWL history and stoneradioopacity) were similar between two groups.The mean stone size preoperatively was significantly larger in patients who were treated with PNL (26.33mm.vs24.04mm.; P = .006). In the RIRS group, the mean stone number was significantly higher than PNL group (P <.001).The mean operative, fluoroscopy and hospitalization time were significantly higher in PNL group (P < .001). Thestone-free rate was 93.3% for the PNL group and 73.5% for the RIRS group after first procedure (P < .001). Nomajor complication (Clavien III-V) occurred in the RIRS group. Conclusion: Although the primary treatment method for renal stones ≥ 2cm size is PNL, serious complicationscan be seen. Therefore, RIRS can be an alternative treatment option in the management of renal stones ≥2 cm size.